Validitas dan Kepraktisan Lembar Kerja Peserta Didik Materi Gelombang dan Bunyi Untuk Siswa Sekolah Menengah Pertama - Zahara Lutfiya Azmi; Apit Fathurohman; Leni Marlina (Jurnal Penelitian Pendidikan IPA, 2022)
Student worksheets are one sort of educational material intended to aid students' learning, explore experiences and ideas, and develop students' cognitive, psychomotor, and affective components. As a result, a study of the validity and applicability of the Student Worksheet on waves and sound content for junior high school students was done. The goal of this study was to see if the Student Worksheet was reliable and practical. The research design used in this study is a developmental study. A walkthrough and a questionnaire were employed as research tools. The validity test was said to be quite valid based on the average content aspect of 4.71, language 4.70, and design 4.78, according to the study's findings. While the practicality test was stated to be very practical, the results obtained one to one teacher on the average content aspect of 5, language 5, and design 5. One to one students obtained an average of 4.73 content aspect, 4.33 language, and 4 design ,55. The results of the practicality of the small group of teachers on the aspect of content are on average 4.11, language 4.66, and design 4.44. The small group of students obtained an average of 4.22 in the aspect of content, 4.52 in language, and 4.36 in design. So it can be concluded that the Student Worksheet material waves and sounds for junior high school is very valid and very practical. Furthermore, it can be used for the effectiveness test stage